Pengaruh Motivasi Terhadap Minat Mahasiswa Akuntansi Mengikuti Program Brevet Pajak (Studi Kasus Pada Mahasiswa PTS Di Semarang Tahun 2019) - Saifudin Saifudin; Bella Fazrine Darmawan (JEMAP, 2019)
Taxation Licence Program established to improve the taxation quality of a professional tax consultant in the future. The Taxation Licence program will not produce a professional tax consultant which acceptable by the company if the students did not have high motivation to study about tax in professional way. Based on this background, the objectives of this research is to analyzed if carrier motivation, economic motivation, quality motivation, and social motivation as the independent variable have some effects on accounting students interest to joining in Taxation Licence program as a dependent variable. The sample of this research using direct survey method that distributed to 324 respondents of accounting students in Economics and Business Faculty of Soegijapranata University (UNIKA), Sultan Agung Islamic University (UNISSULA), and Dian Nuswantoro University (UDINUS). Data in this research were obtained using questionnaires and were analyzed. The hypothesis testing in this research using outer model and inner model analysis with SEM PLS release 3. The result of this analysis showed that all of the independent variable, such as career motivation, economic motivation, quality motivation, and social motivation significantly affect accounting students interest to joining in Taxation Licence program. It indicated that a self motivation for having an taxation licence was more competitive than just graduates from undergradute accounting program, so they become more professional and get better career in taxation.